Comparison of Functional Balance and Probability of Falling in the Elderly with and Without a History of Falling Living in Care Centers - Seyyed Mojtaba Tabatabaiasl; Parisa Sedaghati; Fariba Javazi (Islamic Azad University, Hamedan Branch, 2020)
Objective: The purpose of this study was to compare functional balance and probability of fall in elderly with or without history of fall in care centers. Methods: The statistical population of the present study consisted of 30 elderly men and women over 60 years of two elderly nursing centers in rasht. These specimens were selected according to the inclusion criteria and exit criteria. The age range was between 60 and 74 years. Individuals (15 people)were divided into two groups of aged persons (15 persons) and with a history of land (15 people). People who had no history of eating during the last six months have been knocked down in the group without a history of land eating and people who had tripped once or more in the last six months. the evaluation of the balance and the possibility of seniors fall with tests (leaves and time of rise and departure) were carried out. SPSS software was used to analyze the data. from the shayper-vink test to be natural for data distribution, descriptive statistics were used in the form of statistics such as mean, standard deviation, median, change range and direction of data describing and in the deductive statistics section with respect to comparing the variables from independent t-test. Results: Normality test results confirmed normality of data in the variables of performance equilibrium and probability of fall there was a significant difference between functional balance index in the elderly with a history of fall or without the history of fall. there was a meaningful difference between fall risk index in the elderly with a history of fall or without the history of fall. Conclusion: according to the results of this study, individuals with no history of fall in performance balance indices and probability of fall were better than those with history of fall.